CHANGES IN MICROBIAL BIOMASS CARBON, NITROGEN AND GRAIN YIELD OF LOWLAND RICE VARIETIES IN RESPONSE TO ALTERNATE WET AND DRY WATER REGIME IN THE INLAND VALLEY OF DERIVED SAVANNA - Soremi, Paul A. S. (Journal of Agricultural Sciences (Belgrade), 2019)
This study tested the hypothesis that alternate wet and dry (AWD) water regime would increase soil soil microbial biomass carbon (MBC), nitrogen (MBN), microbial count, variations in MBC, MBN and grain yield could be due to varietal differences in a derived savanna. Experiments (a pot and field) were conducted at the Federal University of Agriculture, Abeokuta (Latitude 7 ° 12 ’to 7 ° 20’ N and Longitude 3 ° 20 ’to 3 ° 28’ E), Nigeria in 2015. In both trials The treatments consisted of a water regime [continuous flooding (control) and AWD imposed on lowland rice varieties [(NERICA® L-19 and Ofada (local check)] at the vegetative growth stage in three cycles. The design in both trials was completely randomized and randomized complete block design for the pot and field experiments respectively, at three replicates. In the screen house MBC and MBN was significantly higher in AWD than in continuously flooded soil, especially at the beginning of AWD cycles. This could have caused nutrient pulses to sustain the improved performance of lowland rice under AWD. A converse pattern was observed on the field in the third cycle. Ofadarice had a significantly higher microbial count and MBC (1 cycle) than NERICA L-19, however a converse pattern was observed on MBC (2 and 3 cycles) and MBN (1 cycle). Composition of their rhizodeposition and timing of cycles could have explained the observed varietal differences on MBC and MBN. A converse pattern was observed on the field in the third cycle. Ofadarice had a significantly higher microbial count and MBC (1 cycle) than NERICA L-19, however a converse pattern was observed on MBC (2 and 3 cycles) and MBN (1 cycle). Composition of their rhizodeposition and timing of cycles could have explained the observed varietal differences on MBC and MBN. A converse pattern was observed on the field in the third cycle. Ofadarice had a significantly higher microbial count and MBC (1 cycle) than NERICA L-19, however a converse pattern was observed on MBC (2 and 3 cycles) and MBN (1 cycle). Composition of their rhizodeposition and timing of cycles could have explained the observed varietal differences on MBC and MBN.